STUDY OF LOCAL WISDOM OF COASTAL COMMUNITIES IN JARING HALUS VILLAGE, LANGKAT REGENCY, NORTH SUMATRA PROVINCE - Indah Tria Suci (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Each region, must have stories that contain local wisdom. Because, the stories that exist in the communityarea have characteristics that develop in an area. This paper aims to determine the local wisdom of coastalcommunities in Jaring Halus Village. The method used in this research is literature study in the form ofresearch articles that have been published in related fields. The results of the literature study show that thecommunity in Jaring Halus village has several traditions, beliefs or local wisdom related to environmentalmanagement such as protecting mangrove and coastal ecosystems and knowledge of ecology.